Development of coated peanut separator and frying skillet machine - Yusof, M Sallehuddin; Fadilullah, M Zul Nadzmi; Hassan, Suhaimi; Maksud, M Idris; Yunos, Muhamad Zaini (Penerbit UTHM, 2018)
Coated peanut which known as Kacang Bersalut Istimewa Deqyoung is a product made from groundnut mix with flour and special spices. Currently, there are some issues with the product that slow down the production process. The groundnut is sticking and become like a ping pong size ball and the time consuming to fry is longer. Coated peanut separator and frying skillet machine can overcome the problems and able to increase the production. Furthermore, the machine aim to facilitate workers to carry out their duties and to assist small and medium industries (SMEs) in Malaysia. The design convenient, determination of the material selection and the main components that help to operate the machine are the main aspects have been considered. Design analysis helps to identify the capability of the machine when the forces act at some main parts of the machine. The comparison between manual method and semi-automatic method shows that the production increase. By using semi-automatic method of production, the increment shows almost 84 percent of production compares to manual method.